KNOWLEDGE MANAGEMENT IMPLEMENTATION FOR IMPROVING ORGANIZATIONAL PERFORMANCE IN BPJS KESEHATAN - Purnama Putra, Harry
BPJS (Social Security Administering Body) Kesehatan is a Public Legal Entity that reports directly to the President and has the duty to organize National Health Insurance for all Indonesian people based on the principles of social insurance. BPJS Kesehatan is an implementation of the transformation of PT. Askes (Persero) since January 1, 2014. The transformation of PT Askes (Persero) into BPJS Kesehatan requires organizations to anticipate and respond to fluctuating and unpredictable environmental changes. In organizations, knowledge is one important strategic resource, especially in rapidly changing environmental conditions. Organizations that manage their knowledge assets well are able to withstand changes and will have a competitive advantage. As the organizer of health insurance for all Indonesians, BPJS Kesehatan seeks to provide optimal performance. BPJS Kesehatan realizes the importance of the role of knowledge management in organizations to improve organizational performance. The purpose of this study is to analyze the current conditions in organizations and recommend appropriate knowledge management strategies for organizations. The methodology used in this study is a qualitative research method. This research uses focus group discussion methods and semi-structured interviews. Discussion and interview methods can provide flexibility to the research subjects in expressing their opinions and thoughts so that the data obtained becomes more detailed. Topics covered in discussions and interviews include the current state of the organization in terms of people, processes, technology and governance, as well as obstacles that hinder the implementation of knowledge management in organizations. From the results of discussions and interviews, it appears that the existing knowledge management in BPJS Kesehatan has not been running optimally due to several problems in the aspects of human, process, technology and governance. Therefore, there is a need to update the concepts and strategies of knowledge management so that knowledge management can be a long-term solution to improve organizational performance and organizational competitive advantage. This study recommends five steps for implementing a successful knowledge management program, so that the organization can carry it out gradually and sustainably with guidance on the implementation plan for knowledge management at BPJS Kesehatan.